Hard coat film and laminate film

Plasma processing of the UV-curable resin-based HC layer in laminated films addresses the adhesion issues by achieving a specific surface roughness and temperature difference, ensuring robust adhesion of the inorganic layer.

JP2025011545AActive Publication Date: 2025-01-24NITTO DENKO CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023113726
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-11
Publication Date
2025-01-24
Estimated Expiration
2043-07-11

AI Technical Summary

Technical Problem

The existing laminated films with a hard coat layer formed via ultraviolet curing face issues with insufficient curing due to oxygen inhibition at the surface, leading to a fragile layer with reduced adhesion of the inorganic layer to the substrate film.

Method used

A hard coat film with a UV-curable resin-based HC layer treated using plasma processing to achieve a surface roughness of 0.80 nm to 4.50 nm and a softening temperature difference of 5 °C or less, ensuring robust adhesion of the inorganic layer.

Benefits of technology

The plasma-treated HC layer ensures effective adhesion of the inorganic layer by eliminating the fragile surface layer, enhancing the durability and adhesion properties of the laminated film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025011545000001_ABST
    Figure 2025011545000001_ABST
Patent Text Reader

Abstract

To provide a hard coat film and a laminate film with which it is possible to secure the adhesion of an inorganic material layer formed on a hard coat layer.SOLUTION: A hard coat film X according to the present invention comprises a base film 11 and a hard coat layer 12 on the base film 11. The hard coat layer 12 is a cured substance of a composition containing an ultraviolet curable resin. The surface roughness Sa of a surface 12a of the hard coat layer 12 on the side reverse from the base film 11 is 0.80 nm to 4.50 nm inclusive. The softening temperature of the surface 12a of the hard coat layer 12 is T1(°C). The difference between a softening temperature T2(°C) of the surface 12a after prescribed plasma processing test and the softening temperature T1(°C) is 5°C or less. A laminate film Y according to the present invention comprises the hard coat film X and an inorganic substance layer 20 on the hard coat layer 12 of the hard coat film X.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hard coat film and a laminate film. [Background technology]

[0002] From the viewpoint of weight reduction and high performance of electronic products, various composite materials in which organic materials and inorganic materials are combined have been developed. For example, a laminated film having a base film made of an organic material and an inorganic layer on the base film is known as a composite material. In the manufacturing process of the laminated film, for example, before the inorganic layer is formed on the base film, a hard coat (HC) layer is formed on the inorganic layer side of the base film, and the base film with the HC layer is made into a hard coat film. The HC layer is a layer that makes the exposed surface of the inorganic layer less susceptible to scratches. Technologies related to such hard coat films and laminated films are described, for example, in Patent Document 1 below. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent Publication No. 2022-65437 Summary of the Invention [Problem to be solved by the invention]

[0004] Patent Document 1 describes a laminated film as an anti-reflection film. This laminated film includes an inorganic layer as an anti-reflection layer and a hard coat film supporting the inorganic layer. The hard coat film includes a substrate film and an HC layer on the substrate film. The HC layer contains nanosilica particles. This allows the HC layer to have surface irregularities on the inorganic layer side. According to Patent Document 1, the surface irregularities of the HC layer increase the adhesion of the inorganic layer to the substrate film.

[0005] The HC layer of Patent Document 1 is formed as follows. First, an ultraviolet-curable composition containing an ultraviolet-curable resin and nanosilica particles is prepared. Next, the composition is applied to one side of a substrate film to form a coating film. Next, the coating film is irradiated with ultraviolet light to promote a curing reaction within the coating film, thereby curing the coating film (ultraviolet curing step).

[0006] However, the present inventors have found the following about such an HC layer. In the ultraviolet curing step, part of the curing reaction is inhibited by oxygen on the surface of the coating film on the substrate film opposite the substrate film and in its vicinity (surface region). Therefore, in the surface region, the curing reaction does not proceed sufficiently, and a relatively low molecular weight polymer is produced. This low molecular weight polymer is weaker in terms of mechanical strength than the high molecular weight polymer produced in the internal region (region closer to the substrate film than the surface region). That is, the HC layer formed by the ultraviolet curing step has a weak thin layer on the surface opposite the substrate film and in its vicinity. This weak thin layer reduces the adhesion of the inorganic layer formed on the HC layer to the substrate film.

[0007] The present invention provides a hard coat film and a laminate film that can ensure the adhesion of an inorganic layer formed on a hard coat layer. [Means for solving the problem]

[0008] The present invention [1] includes a hard coat film comprising a base film and a hard coat layer on the base film, the hard coat layer being a cured layer of a composition containing an ultraviolet-curable resin, the surface of the hard coat layer opposite to the base film having a surface roughness Sa of 0.80 nm or more and 4.50 nm or less, the softening temperature of the surface of the hard coat layer being T1, and the difference between the softening temperature T2 of the surface after the following plasma treatment test and the softening temperature T1 is 5° C. or less.

[0009] Plasma treatment test: The surface of the hard coat layer is treated with inductively coupled plasma of oxygen gas generated by applying high frequency power of 13.56 MHz frequency and 5.0 kW power to a low inductance antenna.

[0010] The present invention [2] includes the hard coat film according to the above [1], wherein the ultraviolet-curable resin is at least one selected from the group consisting of an ultraviolet-curable acrylic urethane resin and an ultraviolet-curable acrylic resin.

[0011] The present invention [3] includes the hard coat film according to the above [1] or [2], in which the softening temperature T1 is 105° C. or higher.

[0012] The present invention [4] includes the hard coat film according to any one of the above [1] to [3], wherein the softening temperature T1 is 150° C. or lower.

[0013] The present invention [5] includes a laminate film comprising the hard coat film according to any one of the above [1] to [4] and an inorganic layer on the hard coat layer of the hard coat film. Effect of the Invention

[0014] In the hard coat film of the present invention, as described above, the surface roughness Sa of the surface of the hard coat layer (cured layer of the composition containing an ultraviolet curable resin) opposite to the substrate film is 0.80 nm or more and 4.50 nm or less, and the difference (|T2-T1|) between the softening temperature T1 of the surface of the hard coat (HC) layer and the softening temperature T2 of the surface after the plasma treatment test is 5°C or less. The surface roughness Sa of the HC layer being 0.80 nm or more and 4.50 nm or less means that when an inorganic layer is formed on the HC layer, the anchor effect of the HC layer on the inorganic layer enhances the adhesion of the inorganic layer to the hard coat film. In addition, the softening temperature difference being 5°C or less indicates that the HC layer does not substantially have the above-mentioned fragile thin layer. Therefore, the hard coat film of the present invention can ensure the adhesion of the inorganic layer formed on the HC layer. The laminate film of the present invention having such a hard coat film can ensure the adhesion of the inorganic layer on the hard coat layer. [Brief description of the drawings]

[0015] [Figure 1] 1 is a schematic cross-sectional view of one embodiment of a hard coat film of the present invention. [Diagram 2] 1 is a schematic cross-sectional view of one embodiment of a laminated film of the present invention. [Diagram 3] FIG. 2 shows a case where the inorganic layer of the laminated film has a laminated structure of an adhesive layer and an antireflection layer. [Figure 4] 4 shows an example of a method for producing the laminated film shown in Fig. 2. Fig. 4A shows a cured resin layer forming step, Fig. 4B shows a plasma treatment step, and Fig. 4C shows an inorganic layer forming step. [Diagram 5] 3 is a schematic diagram of an apparatus for carrying out a plasma treatment step and a film formation step in the example of the method for producing the laminated film shown in FIG. 2. FIG. [Figure 6] 6 is a perspective view showing the positional relationship between a low inductance antenna and a base film in the plasma processing chamber shown in FIG. 5. [Figure 7]6 is a cross-sectional view showing the positional relationship between a low inductance antenna and a base film in the plasma processing chamber shown in FIG. 5. [Figure 8] A method for measuring the softening temperature of the surface of a hard coat layer by nano thermal analysis will be described. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] 1, a hard coat film X according to one embodiment of the present invention includes a base film 11 and a hard coat (HC) layer 12 in this order in a thickness direction H. The HC layer 12 is disposed on the base film 11. That is, the base film 11 and the HC layer 12 are in contact with each other. The hard coat film X extends in a direction (plane direction D) perpendicular to the thickness direction H.

[0017] The base film 11 is an element that ensures the strength of the hard coat film X. The base film 11 is, for example, a transparent resin film having flexibility. Examples of the material of the base film 11 include polyester resin, polyolefin resin, cellulose resin, acrylic resin, polycarbonate resin, polyethersulfone resin, polyarylate resin, melamine resin, polyamide resin, polyimide resin, and polystyrene resin. Examples of the polyester resin include polyethylene terephthalate (PET), polybutylene terephthalate, and polyethylene naphthalate. Examples of the polyolefin resin include polyethylene, polypropylene, and cycloolefin polymer (COP). Examples of the cellulose resin include triacetyl cellulose (TAC). These materials may be used alone, or two or more types may be used in combination. From the viewpoint of transparency and strength, the material of the base film 11 is preferably at least one selected from the group consisting of polyester resin, polyolefin resin, and cellulose resin, and more preferably at least one selected from the group consisting of PET, COP, and TAC. In addition, the base film 11 does not contain particles in this embodiment.

[0018] The thickness of the base film 11 is preferably 10 μm or more, more preferably 20 μm or more, and even more preferably 30 μm or more, and is preferably 200 μm or less, more preferably 150 μm or less, and even more preferably 100 μm or less. When the thickness of the base film 11 is equal to or more than the above lower limit, the strength of the hard coat film X can be ensured. When the thickness of the base film 11 is equal to or less than the above upper limit, the handleability of the hard coat film X in the roll-to-roll process described below can be ensured. In addition, a carrier film (not shown) may be attached to the back surface of the base film 11 (the surface opposite to the HC layer 12) in order to ensure the transportability and handleability of the base film 11 in the roll-to-roll process.

[0019] The total light transmittance (JIS K 7375:2008) of the base film 11 is preferably 80% or more, more preferably 90% or more, and even more preferably 95% or more, and is, for example, 100% or less. When the total light transmittance of the base film 11 is the above-mentioned lower limit or more, good transparency can be ensured in the hard coat film X.

[0020] The HC layer 12 is a layer that makes it difficult for scratches to form on the exposed surface of a layer (inorganic layer 20 in the embodiment shown in FIG. 2) formed on the HC layer 12. The HC layer 12 is a cured layer of a composition containing an ultraviolet-curable resin (ultraviolet-curable resin composition).

[0021] Examples of ultraviolet curing resins include polyester resins, acrylic urethane resins, acrylic resins (excluding acrylic urethane resins), urethane resins (excluding acrylic urethane resins), amide resins, silicone resins, epoxy resins, and melamine resins. These resins may be used alone or in combination of two or more. From the viewpoint of ensuring the hardness of the HC layer 12, the ultraviolet curing resin is at least one selected from the group consisting of ultraviolet curing acrylic urethane resins and ultraviolet curing acrylic resins.

[0022] The amount of inorganic oxide particles contained in the HC layer 12 is preferably small. The smaller the amount of inorganic oxide particles in the HC layer 12, the more the scattering of light incident on the hard coat film X caused by particles can be suppressed, and the manufacturing cost of the hard coat film X can be reduced. Examples of materials for inorganic oxide particles include silica, alumina, titania, zirconia, calcium oxide, tin oxide, indium oxide, cadmium oxide, and antimony oxide. The content of inorganic oxide particles in the HC layer 12 is preferably 20% by mass or less, more preferably 10% by mass or less, even more preferably 5% by mass or less, even more preferably 1% by mass or less, even more preferably 0.5% by mass or less, even more preferably 0.2% by mass or less, even more preferably 0.1% by mass or less, and particularly preferably 0.0% by mass.

[0023] The thickness of the HC layer 12 is preferably 1 μm or more, more preferably 3 μm or more, and even more preferably 5 μm or more, and is preferably 30 μm or less, more preferably 25 μm or less, and even more preferably 20 μm or less. When the thickness of the HC layer 12 is equal to or more than the above lower limit, the scratch resistance of the HC layer 12 can be ensured. When the thickness of the HC layer 12 is equal to or less than the above upper limit, the transparency of the HC layer 12 can be ensured.

[0024] The HC layer 12 has a surface 12a on the opposite side to the substrate film 11. The surface roughness Sa (arithmetic mean height based on ISO 25178-2:2012) of the surface 12a is preferably 0.80 nm or more, more preferably 1.00 nm or more, even more preferably 1.20 nm or more, and is preferably 4.50 nm or less, more preferably 3.50 nm or less, even more preferably 3.00 nm or less, even more preferably 2.50 nm or less, and more preferably 2.00 nm or less. When the surface roughness Sa of the surface 12a is equal to or more than the above lower limit, the adhesion of the layer formed on the surface 12a (inorganic layer 20 in the embodiment shown in FIG. 2) to the hard coat film X is enhanced due to the anchor effect of the fine irregularities of the surface 12a. When the surface roughness Sa of the surface 12a is equal to or less than the above upper limit, excessive irregularities on the surface 12a can be suppressed to ensure mechanical strength.

[0025] In this embodiment, the surface 12a is a plasma-treated surface. From the viewpoint of reducing the softening temperature difference (|T2-T1|) described below, the plasma treatment is preferably a treatment by inductively coupled plasma using an oxygen-containing gas generated by application of high-frequency power to a low-inductance antenna (oxygen-LAICP treatment). The oxygen-LAICP treatment of the surface 12a will be described specifically in the manufacturing method of the laminated film Y (shown in FIG. 2) later.

[0026] The surface 12a of the HC layer 12 has a softening temperature T1 (°C). The surface 12a has a softening temperature T2 (°C) after the plasma treatment test described below. The softening temperatures T1 and T2 refer to softening temperatures measured by nano thermal analysis. Nano thermal analysis is an analysis method for measuring the thermal properties (softening temperature, glass transition point, etc.) of a sample surface on a nanoscale by contacting the sample surface with a temperature-adjustable microcantilever as a probe. The method for measuring the softening temperatures T1 and T2 by nano thermal analysis and the method for the plasma treatment test are specifically described below in relation to the examples.

[0027] Plasma treatment test: The surface of the hard coat layer is treated with inductively coupled plasma of oxygen gas generated by applying high frequency power of 13.56 MHz frequency and 5.0 kW power to a low inductance antenna.

[0028] The difference (|T2-T1|) between the softening temperature T2 and the softening temperature T1 is 5° C. or less, preferably 4° C. or less, for example, 0° C. or more. The difference between the softening temperature T2 and the softening temperature T1 being 5° C. or less indicates that the HC layer 12 does not substantially have the above-mentioned brittle thin layer on the surface 12a.

[0029] The softening temperature T1 is preferably 105° C. or higher, more preferably 115° C. or higher, and even more preferably 125° C. or higher, and is preferably 150° C. or lower, more preferably 140° C. or lower, and even more preferably 130° C. or lower. When the softening temperature T1 is equal to or higher than the lower limit, the brittle thin layer on the surface of the HC layer 12 is sufficiently removed, and the adhesion of the inorganic layer to the hard coat film X can be ensured. When the softening temperature T1 is equal to or lower than the upper limit, the flexibility of the hard coat film X is ensured, and the occurrence of cracks in the HC layer 12 during film transport can be suppressed.

[0030] The total light transmittance (JIS K 7375:2008) of the hard coat film X is preferably 80% or more, more preferably 90% or more, and even more preferably 95% or more, and is, for example, 100% or less. When the total light transmittance of the hard coat film X is the above-mentioned lower limit or more, good transparency can be ensured in the hard coat film X.

[0031] In the hard coat film X, as described above, the surface roughness Sa of the surface 12a of the HC layer 12 (cured layer of a composition containing an ultraviolet-curable resin) opposite to the base film 11 is 0.80 nm or more and 4.50 nm or less, and the difference (|T2-T1|) between the softening temperature T1 of the surface 12a of the HC layer 12 and the softening temperature T2 of the surface 12a after the plasma treatment test is 5°C or less. The surface roughness Sa of the HC layer 12 being 0.80 nm or more and 4.50 nm or less means that when an inorganic layer is formed on the HC layer 12, the HC layer 12 has an anchor effect on the inorganic layer, thereby enhancing the adhesion of the inorganic layer to the hard coat film X. In addition, the softening temperature difference being 5°C or less indicates that the HC layer 12 does not substantially have the above-mentioned fragile thin layer. Therefore, the hard coat film X can ensure the adhesion of the inorganic layer formed on the HC layer 12.

[0032] 2 is a cross-sectional schematic diagram of a laminated film Y according to one embodiment of the present invention. The laminated film Y includes a hard coat film X and an inorganic layer 20 on the hard coat film X. Specifically, the inorganic layer 20 is disposed on the HC layer 12 of the hard coat film X. The inorganic layer 20 and the HC layer 12 are in contact with each other. Such a laminated film Y extends in a direction (plane direction D) perpendicular to the thickness direction H.

[0033] Examples of the inorganic layer 20 include an anti-reflective layer and a conductive layer. The anti-reflective layer is a layer having anti-reflective properties that suppresses the reflection intensity of external light. The conductive layer is a layer having conductivity. The inorganic layer 20 may be another layer. The inorganic layer 20 may also be a composite layer including an anti-reflective layer and another layer. The inorganic layer 20 may also be a composite layer including a conductive layer and another layer. FIG. 3 shows a case where the inorganic layer 20 has a laminated structure of an adhesive layer 21 and an anti-reflective layer 22.

[0034] The adhesive layer 21 is disposed on the HC layer 12 of the hard coat film X. Specifically, the adhesive layer 21 is disposed on the surface 12a of the HC layer 12. The adhesive layer 21 is in contact with the HC layer 12. The adhesive layer 21 is a layer that enhances the adhesion of the inorganic layer 20 to the hard coat film X. Examples of materials for the adhesive layer 21 include metals such as Si, In, Ni, Cr, Ar, Sn, Au, Ag, Pt, Zn, Ti, W, Zr, Pd, and Nb, alloys of two or more of these metals, and oxides of these metals. From the viewpoint of achieving both the adhesiveness to both the hard coat film X and the inorganic layer 20 and the transparency of the adhesive layer 21, the adhesive layer 21 is preferably an inorganic oxide film containing at least one element selected from the group consisting of Si, In, Al, Sn, Ti, and Zr. From the viewpoint of achieving both adhesion to both the hard coat film X and the inorganic layer 20 and transparency of the adhesion layer 21, indium tin composite oxide (ITO) or silicon oxide (SiOx) is more preferable as the material of the adhesion layer 21. The silicon oxide as the material of the adhesion layer 21 is preferably SiOx having a smaller amount of oxygen than the stoichiometric composition, and more preferably SiOx where x is 1.2 or more and 1.9 or less.

[0035] The thickness of the adhesive layer 21 is preferably 1 nm or more, more preferably 2 nm or more, and even more preferably 3 nm or more, and is preferably 50 nm or less, more preferably 30 nm or less, even more preferably 10 nm or less, and even more preferably 5 nm or less. When the thickness of the adhesive layer 21 is equal to or more than the lower limit, the adhesive strength between the hard coat film X and the inorganic layer 20 can be ensured. When the thickness of the adhesive layer 21 is equal to or less than the upper limit, the transparency of the adhesive layer 21 can be ensured.

[0036] The antireflection layer 22 is disposed on one surface of the adhesive layer 21 in the thickness direction H. The antireflection layer 22 preferably includes a plurality of transparent inorganic oxide films laminated in the thickness direction H. FIG. 3 shows an example of such an antireflection layer 22. The antireflection layer 22 in FIG. 3 includes a high refractive index layer 22a, a low refractive index layer 22b, a high refractive index layer 22c, and a low refractive index layer 22d in this order from the adhesive layer 21 side in the thickness direction H. The high refractive index layer 22a contacts the adhesive layer 21. The high refractive index layer 22a contacts the low refractive index layer 22b. The low refractive index layer 22b contacts the high refractive index layer 22c. The high refractive index layer 22c contacts the low refractive index layer 22d. The high refractive index layers 22a and 22c are layers with a relatively high refractive index, and the low refractive index layers 22b and 22d are layers with a relatively low refractive index. In such a laminated structure, the intensity of the reflected light is attenuated by the interference between the reflected light at multiple interfaces in the high refractive index layers 22a, 22c and the low refractive index layers 22b, 22d. Such interference can be realized by adjusting the optical film thickness (the product of the refractive index and the thickness of the film) of each layer of the inorganic layer 20.

[0037] The high refractive index layer 22a (first high refractive index layer) is made of a high refractive index material having a refractive index of preferably 1.9 or more at a wavelength of 550 nm. Examples of the high refractive index material include niobium oxide (Nb2O5), titanium oxide, zirconium oxide, indium tin oxide (ITO), and antimony tin oxide (ATO). From the viewpoint of achieving both a high refractive index and low absorption of visible light, the high refractive index material is preferably niobium oxide (refractive index 2.33). The optical thickness of the high refractive index layer 22a is, for example, 20 nm or more and, for example, 55 nm or less.

[0038] The low refractive index layer 22b (first low refractive index layer) is made of a low refractive index material having a refractive index of preferably 1.6 or less at a wavelength of 550 nm. Examples of the low refractive index material include silicon dioxide (SiO2) and magnesium fluoride. From the viewpoint of achieving both a low refractive index and low absorption of visible light, the low refractive index material is preferably silicon dioxide (refractive index 1.46). The optical film thickness of the low refractive index layer 22b is, for example, 15 nm or more and, for example, 70 nm or less.

[0039] The high refractive index layer 22c (second high refractive index layer) is made of a high refractive index material having a refractive index of preferably 1.9 or more at a wavelength of 550 nm. Examples of the high refractive index material include the materials described above for the high refractive index layer 22a, and niobium oxide is preferred. The optical thickness of the high refractive index layer 22c is, for example, 60 nm or more and, for example, 330 nm or less.

[0040] The low refractive index layer 22d (second low refractive index layer) is made of a low refractive index material having a refractive index of preferably 1.6 or less at a wavelength of 550 nm. Examples of the low refractive index material include the materials described above for the low refractive index layer 22b, and silicon dioxide is preferred. The optical thickness of the low refractive index layer 22d is, for example, 100 nm or more and, for example, 160 nm or less.

[0041] The total thickness of the antireflection layer 22 is preferably 180 nm or more, more preferably 200 nm or more, and even more preferably 220 nm or more, and is preferably 320 nm or less, more preferably 280 nm or less, and even more preferably 250 nm or less. In this embodiment, the total thickness of the antireflection layer 22 is the sum of the thicknesses of the high refractive index layers 22a, 22c and the low refractive index layers 22b, 22d. When the total thickness of the antireflection layer 22 is equal to or greater than the lower limit, the antireflection layer 22 can ensure the function of attenuating the reflected light intensity. When the total thickness of the antireflection layer 22 is equal to or less than the upper limit, cracking of the antireflection layer 22 can be suppressed.

[0042] When the inorganic layer 20 includes a conductive layer, the conductive layer is formed from a conductive material. Examples of the conductive material include metals and metal oxides. Examples of the metals include copper, silver, gold, and alloys thereof. Examples of the metal oxides include indium-containing conductive oxides and antimony-containing conductive oxides. Examples of the indium-containing conductive oxides include indium tin composite oxide (ITO), indium zinc composite oxide (IZO), indium gallium composite oxide (IGO), and indium gallium zinc composite oxide (IGZO). Examples of the antimony-containing conductive oxides include antimony tin composite oxide (ATO).

[0043] The peeling rate of the inorganic layer 20 of the laminated film Y in the second test described below after the first test (accelerated weather resistance test) described below is preferably 5% or less, more preferably 3% or less, and even more preferably 1% or less, from the viewpoint of ensuring the adhesion of the inorganic layer 20. More specifically, the methods of the first and second tests are as described later in the examples. When the peeling rate of the inorganic layer 20 is equal to or less than the upper limit, the substantial deterioration of the function of the inorganic layer 20 due to peeling of the inorganic layer 20 can be suppressed.

[0044] Test 1: First, the side of the hard coat film X in the laminate film Y is fixed to a glass plate. Next, the inorganic layer 20 of the laminate film Y on the glass plate is irradiated with light at a temperature of 85° C., a relative humidity of 45%, and an irradiation intensity (integrated illuminance at 290 nm to 450 nm) of 150 mW / cm 2 2 The specimen is exposed to light for 32.5 hours under the above conditions.

[0045] Test 2: First, eleven parallel first incisions (1 mm apart) extending linearly in a first direction and eleven parallel second incisions (1 mm apart) extending linearly in a second direction perpendicular to the first direction are formed with a cutter knife in the inorganic layer 20 and the adhesive layer 21 of the laminated film Y on the glass plate after the first test, and 100 grids are formed by the first and second incisions. Next, isopropyl alcohol is continuously dripped at 2 mL / min onto the 100 grid areas of the laminated film Y, while a polyester wiper is slid over the area under the following conditions: wiper contact surface 20 mm x 20 mm, load 1.5 kg / 20 mm, sliding speed 50 mm / sec, and 1000 reciprocations. Next, 1 mm of the 100 grids are cut into 1 mm squares. 2 The number of squares where the above peeling occurred is counted. The counted number is then divided by 100 to calculate the peeling rate (%).

[0046] As described above, the laminated film Y includes the hard coat film X and the inorganic layer 20 on the HC layer 12 of the hard coat film X. As described above, in the hard coat film X, the surface roughness Sa of the surface 12a of the HC layer 12 (cured layer of a composition containing an ultraviolet-curable resin) on the side opposite to the base film 11 is 0.80 nm or more and 4.50 nm or less, and the difference (|T2-T1|) between the softening temperature T1 of the surface 12a of the HC layer 12 and the softening temperature T2 of the surface 12a after the plasma treatment test is 5° C. or less. Therefore, the laminated film Y can ensure the adhesion of the inorganic layer 20 on the HC layer 12, similar to the above-mentioned hard coat film X.

[0047] 4A to 4C show an example of a method for producing the laminated film Y. This production method includes a cured resin layer forming step (FIG. 4A), a plasma treatment step (FIG. 4B), and a film forming step (FIG. 4C).

[0048] In the cured resin layer forming step, as shown in FIG. 4A, an HC layer 12' is formed on a long substrate film 11. This results in a hard coat film X'. The HC layer 12' can be formed by applying the above-mentioned ultraviolet curable resin composition to the substrate film 11 to form a coating film, and then curing the coating film. The ultraviolet curable resin composition may contain other components other than the above-mentioned ultraviolet curable resin as necessary. Examples of the other components include a solvent, a photopolymerization initiator, and a leveling agent. Examples of the solvent include butyl acetate, ethyl acetate, toluene, and cyclopentanone.

[0049] When the ultraviolet-curable resin composition contains a solvent, the coating film on the substrate film 11 is dried after the ultraviolet-curable resin composition is applied. The drying temperature is, for example, 50° C. or higher and, for example, 120° C. or lower. The drying time is, for example, 10 seconds or longer and, for example, 10 minutes or shorter. The coating film on the substrate film 11 is cured by ultraviolet irradiation. Examples of the light source for ultraviolet irradiation include a high-pressure mercury lamp and an LED light. The integrated irradiation amount of ultraviolet light is, for example, 100 mJ / cm. 2 or more, for example, 500 mJ / cm 2 The following is the result.

[0050] In this manner, a long hard coat film X' can be produced. In this embodiment, a roll of the long hard coat film X' is prepared. Specifically, the hard coat film X' is wound so that the surface of the hard coat film X' on the HC layer 12' side faces inward in the roll radial direction.

[0051] In this manufacturing method, next, a plasma treatment process and a film formation process are carried out in sequence while the hard coat film X' is transported as a workpiece film W by a roll-to-roll method under a reduced pressure atmosphere. The device Z shown in Fig. 5 is an example of a device for carrying out the plasma treatment process and the film formation process. The device Z includes a payout chamber R1, a winding chamber R2, a connection chamber C1, a plasma treatment chamber C2, a connection chamber C3, a film formation chamber C4, a connection chamber C5, a connection chamber C6, and a PEM device (not shown).

[0052] The pay-out chamber R1 is equipped with a pay-out roller 51 for paying out the workpiece film W. A roll of a long hard-coated film X' is attached to the pay-out roller 51 as the workpiece film W. In addition, a predetermined number of guide rollers G for guiding the workpiece film W are provided in the pay-out chamber R1.

[0053] The winding chamber R2 is equipped with a winding roller 52 for winding up the workpiece film W. A predetermined number of guide rollers G for guiding the workpiece film W are provided in the winding chamber R2.

[0054] The connecting chamber C1 is disposed next to the pay-out chamber R1 in the running direction of the workpiece film W, and disposed before the plasma processing chamber C2. A predetermined number of guide rollers G for guiding the workpiece film W are provided in the connecting chamber C1. The connecting chamber C1 is connected to a vacuum pump (not shown), and is configured so that the pressure inside the connecting chamber C1 can be adjusted. When the device Z is in operation, the pressure inside the connecting chamber C1 is maintained at a predetermined pressure between the pressure inside the pay-out chamber R1 and the pressure inside the plasma processing chamber C2. This ensures a pressure difference between the pay-out chamber R1 and the plasma processing chamber C2.

[0055] The plasma processing chamber C2 is disposed between the connecting chamber C1 and the connecting chamber C3 in the running direction of the workpiece film W. In the plasma processing chamber C2, a plasma processing step is carried out as described below.

[0056] In this embodiment, the plasma processing chamber C2 is equipped with a plurality of low inductance antennas (LA) 71. The low inductance antenna means an antenna that has a low inductance of 7.5 μH or less and can generate inductively coupled plasma by applying high frequency power. In this embodiment, the LA 71 is supported by a mounting fixture 72 and covered by a cover block 73 (not shown in FIG. 6) as shown in FIG. 6 and FIG. 7, and is disposed inside the plasma processing chamber C2 (a case where the number of LA 71 is four is illustrated as an example).

[0057] The multiple LAs 71 are aligned in the travel direction of the workpiece film W and in a direction perpendicular to the travel direction (the width direction of the workpiece film W). The fixture 72 is a vacuum flange. The LAs 71 are fixed to the fixture 72 via a feedthrough 74 as shown in FIG. 7. The fixture 72 is assembled to an opening 75 provided in the wall of the plasma processing chamber C2 as shown in FIG. 5. Specifically, the fixture 72 is assembled to the opening 75 with a seal member (not shown) sandwiched between the wall of the plasma processing chamber C2 and the fixture 72. The LAs 71 are electrically connected to a high-frequency power source (RF power source) outside the plasma processing chamber C2 via an impedance matching device. Such an LAs 71 is formed of a conductor. Examples of the conductor include copper and silver, and copper is preferable. The LAs 71 may be covered with an insulator. Examples of the insulator include glass and quartz.

[0058] The cover block 73 includes a block body 73A and a plurality of partition plates 73B. The block body 73A has a plurality of storage spaces 73a. Each storage space 73a stores one LA 71. The partition plates 73B are arranged to close the storage spaces 73a. The storage spaces 73a are sealed spaces. In the cover block 73, the block body 73A is made of, for example, aluminum. Examples of aluminum include aluminum A5052. The partition plates 73B are made of an insulating material. Examples of insulating materials include quartz and glass. The separation distance d' (shown in FIG. 7) between the workpiece film W traveling in the plasma processing chamber C2 and the cover block 73 is, for example, 50 to 200 mm. Such a cover block 73 helps to avoid damage and contamination of the LA 71 due to plasma processing without excessively reducing the plasma conversion efficiency due to the power applied to the LA 71, and also helps to suppress damage to the workpiece film W being plasma processed.

[0059] As shown in FIG. 6, the LA71 has an open loop shape in this embodiment. The open loop shape of the LA71 is advantageous in lowering the inductance of the LA71. Therefore, the open loop shape of the LA71 can suppress an increase in voltage due to an increase in the power applied to the LA71. This can suppress abnormal discharge during plasma processing, which will be described later. By suppressing abnormal discharge, damage to the hard coat film X' (work film W) to be plasma processed can be suppressed. Specifically, the LA71 has a U-shape having two free ends. For each LA71, the two free ends are fixed to the mounting fixture 72 so as to be aligned in the width direction of the work film W. In addition, in this embodiment, the LA71 has an extension portion 71a on the opposite side to the two free ends. The extension portion 71a extends parallel to the work film W passing through the plasma processing chamber C2. The extension portion 71a extends in the width direction of the work film W. Each extension 71a may extend in the running direction of the workpiece film W (four LAs 71 may be arranged in this manner). The length of the extension 71a is, for example, 50 to 150 mm (FIG. 6 illustrates an example in which the length of the extension 71a is the same as the maximum length d2 of the LA71, which will be described later). The LA71 may have a coil shape instead of an open loop shape.

[0060] The LA 71 extends from the fixture 72 toward the workpiece film W. The LA 71 preferably extends perpendicularly to the fixture 72. The extension length d1 of the LA 71 from the fixture 72 is, for example, 30 to 150 mm. The maximum length d2 of the LA 71 in the surface direction of the workpiece film W is, for example, 50 to 150 mm. The separation distance d3 (shown in FIG. 7) between the LA 71 and the workpiece film W is, for example, 50 to 200 mm. The extension length d1 and the separation distance d3 are preferably the same. The ratio (d3 / d1) of the separation distance d3 to the extension length d1 is, for example, 0.5 to 3.5. The number (number of rows) of the LA 71 arranged at a distance in the running direction of the workpiece film W may be 1, 2, or 3 depending on the running speed (i.e., plasma processing time) of the workpiece film W, or may be 4 or more if necessary. In the running direction of the workpiece film W, the center distance d4 between adjacent LAs 71 is, for example, 100 to 500 mm. In the width direction of the workpiece film W, the center distance d5 between adjacent LAs 71 is, for example, 200 to 500 mm. By adjusting the center distance d5, the uniformity of the plasma density in the width direction of the workpiece film W described later can be controlled. The center distance d4 and the center distance d5 are preferably the same. The ratio (d5 / d4) of the center distance d5 to the center distance d4 is, for example, 0.5 to 2.0. The center points of the extensions 71a of the four LAs 71 preferably form a square with the vertices as vertices. Such a set of LAs 71 can generate high-density plasma. For the LAs 71, for example, a high-frequency antenna for plasma generation described in JP 2013-258153 A may be used.

[0061] In this embodiment, the plasma processing chamber C2 further includes a transport roller 53. The transport roller 53 is a main guide roller for transporting the workpiece film W in the plasma processing chamber C2. The transport roller 53 has a temperature adjustment function that can heat or cool the workpiece film W. In other words, the transport roller 53 is a transport roller with a temperature adjustment function. When the device Z is in operation, the transport roller 53 transports the workpiece film W while contacting the back surface (the surface opposite to the HC layer 12) of the workpiece film W. The LA71 is disposed opposite the transport roller 53. According to the device Z having such a plasma processing chamber C2, in the plasma processing step S2, the transport roller 53 with a temperature adjustment function that contacts the workpiece film W can perform plasma processing on the workpiece film W while cooling or heating the workpiece film W. By controlling the temperature of the workpiece film W, thermal deformation of the workpiece film W can be suppressed, and the influence of the thermal deformation on the transport of the workpiece film W can be suppressed.

[0062] The PEM device is a device for performing plasma emission monitoring (PEM) during plasma processing, and includes a device body and an optical fiber for collecting light. The tip (one end) of the optical fiber is disposed between the workpiece film W and LA71 in the plasma processing chamber C2. The other end of the optical fiber is connected to the device body. In addition, a first line L1 equipped with a flow rate control valve for introducing gas into the chamber is connected to the plasma processing chamber C2.

[0063] The connecting chamber C3 is disposed next to the plasma processing chamber C2 in the running direction of the workpiece film W and disposed before the film forming chamber C4. A predetermined number of guide rollers G for guiding the workpiece film W are provided in the connecting chamber C3. The connecting chamber C3 is connected to a vacuum pump (not shown) and is configured to be able to adjust the pressure inside the chamber. When the device Z is in operation, the pressure inside the connecting chamber C3 is maintained at a predetermined pressure between the pressure inside the plasma processing chamber C2 and the pressure inside the film forming chamber C4. This ensures a pressure difference between the plasma processing chamber C2 and the film forming chamber C4.

[0064] The film-forming chamber C4 is disposed next to the connection chamber C3 in the running direction of the workpiece film W. The film-forming chamber C4 is connected to a vacuum pump (not shown) and is configured to be able to adjust the interior of the chamber to a predetermined vacuum level. In the film-forming chamber C4, a film-forming process is carried out as described below.

[0065] In this embodiment, the film forming chamber C4 is a sputtering film forming chamber. The film forming chamber C4 includes a film forming roller 54 and a plurality of sputtering chambers 60 (sputtering chambers 60a to 60e) (a case where the number of sputtering chambers 60 is 5 is illustrated as an example). The film forming roller 54 is a main guide roller for transporting the workpiece film W in the film forming chamber C4. The film forming roller 54 has a temperature adjustment function capable of heating or cooling the workpiece film W. The sputtering chamber 60 is a space partitioned in the film forming chamber C4. The plurality of sputtering chambers 60 are arranged along the circumferential direction of the film forming roller 54. Each sputtering chamber 60 opens toward the film forming roller 54. A cathode 61 is provided in the sputtering chamber 60. A target (not shown) is arranged on the cathode 61 as a film forming material supply material. The target is arranged on the target so as to face the film forming roller 54. Each sputtering chamber 60 is provided with a power supply (not shown) for applying a voltage to the target to generate a glow discharge. Examples of power supplies include a DC power supply, an AC power supply, an MF power supply, an RF power supply, and an MF-AC power supply. An MF-AC power supply refers to an AC power supply with a frequency band of several kHz to several MHz. A required number of second lines (not shown) with flow rate control valves for introducing gas into the chamber are connected to each sputtering chamber 60. In addition, a predetermined number of guide rollers G for guiding the workpiece film W are provided in the film formation chamber C4.

[0066] The connecting chamber C5 and the connecting chamber C6 are arranged in this order between the film forming chamber C4 and the winding chamber R2 in the running direction of the workpiece film W. A predetermined number of guide rollers G for guiding the workpiece film W are provided in the connecting chamber C5. A predetermined number of guide rollers G for guiding the workpiece film W are provided in the connecting chamber C6. The connecting chamber C5 is connected to a vacuum pump (not shown) and is configured to be able to adjust the pressure inside the connecting chamber C5. The connecting chamber C6 is connected to a vacuum pump (not shown) and is configured to be able to adjust the pressure inside the connecting chamber C5. When the device Z is in operation, the pressure inside the connecting chambers C5 and C6 is maintained at a predetermined pressure between the pressure inside the film forming chamber C4 and the pressure inside the winding chamber R2. This ensures a pressure difference between the film forming chamber C4 and the winding chamber R2.

[0067] A plasma processing step and a film forming step are carried out in sequence by the above-described apparatus Z. Specifically, the steps are as follows.

[0068] The workpiece film W is unwound from the unwinding chamber R1. After being unwound from the unwinding chamber R1, the workpiece film W passes through the connecting chamber C1, the plasma processing chamber C2, the connecting chamber C3, the film forming chamber C4, the connecting chamber C5, and the connecting chamber C6 in sequence, and is wound up in the winding chamber R2. The running speed of the workpiece film W is, for example, 0.5 m / min or more, and, for example, 5 m / min or less. In addition, the series of lines from the unwinding chamber R1 to the winding chamber R2 is not open to the atmosphere along the way, and the process is carried out in the line under a reduced pressure atmosphere. The reduced pressure atmosphere is preferably under vacuum. Under vacuum preferably means a reduced pressure atmosphere of 7 Pa or less.

[0069] In the plasma processing chamber C2, a plasma processing step is carried out. In the plasma processing step, in a reduced pressure atmosphere in the plasma processing chamber C2 (chamber), the workpiece film W is plasma-processed while detecting the plasma emission intensity. In this embodiment, the plasma processing is a process using inductively coupled plasma of an oxygen-containing gas (oxygen-LAICP process) generated by applying high-frequency power to the LA71. Specifically, it is as follows.

[0070] Oxygen is supplied into the plasma processing chamber C2 during plasma processing through the first line L1. In addition to oxygen, an inert gas may be supplied into the plasma processing chamber C2. Examples of the inert gas include argon, krypton, and xenon. The gas in the plasma processing chamber C2 may contain other gases besides the inert gas. Examples of the other gases include oxygen, nitrogen, hydrogen, and water vapor. The oxygen concentration of the gas (oxygen-containing gas) in the plasma processing chamber C2 is preferably 30% by volume or more, more preferably 50% by volume or more, even more preferably 80% by volume or more, even more preferably 90% by volume or more, even more preferably 95% by volume or more, and particularly preferably 100% by volume. When the oxygen concentration is equal to or more than the lower limit, a high-density oxygen plasma can be generated. This is useful for forming nanometer-order fine irregularities on the surface of the workpiece film W and for highly activating the surface by cleaning it.

[0071] The pressure (first pressure) in the plasma processing chamber C2 during plasma processing is preferably 0.1 Pa or more, more preferably 0.2 Pa or more, even more preferably 0.3 Pa or more, and is preferably 7 Pa or less, more preferably 5 Pa or less, even more preferably 3 Pa or less. When the first pressure is equal to or greater than the above-mentioned lower limit, a plasma environment of sufficient density for surface modification processing of the workpiece film W can be formed in the plasma processing chamber C2 in the plasma processing. When the first pressure is equal to or less than the above-mentioned upper limit, damage to the workpiece film W caused by excessively high-density plasma can be suppressed in the plasma processing. The first pressure can be adjusted by the amount of oxygen gas supplied into the plasma processing chamber C2.

[0072] The frequency of the high frequency power applied to the LA71 during plasma processing is preferably 1 MHz or more, more preferably 5 MHz or more, and even more preferably 10 MHz or more, and is also preferably 100 MHz or less, more preferably 80 MHz or less, and even more preferably 60 MHz or less. When the frequency is equal to or more than the lower limit, the plasma discharge can be stabilized while increasing the plasma current density in the plasma processing. When the frequency is equal to or less than the upper limit, the antenna potential can be suppressed, and therefore damage to the workpiece film W caused by the plasma can be suppressed. Moreover, the high frequency power is preferably 0.1 kW or more, more preferably 0.3 kW or more, and even more preferably 1.0 kW or more, and is also preferably 10 kW or less, more preferably 8 kW or less, and even more preferably 6 kW or less. When the high frequency power is equal to or more than the lower limit, a high density plasma environment can be formed in the plasma processing chamber C2 in the plasma processing by inductively coupled plasma. When the high frequency power is equal to or less than the upper limit, excessive damage to the workpiece film W caused by the plasma can be suppressed.

[0073] In the plasma treatment step, the plasma emission intensity during the plasma treatment is preferably monitored by a PEM device, and the amount of oxygen gas introduced, the high frequency power, the travel speed, and the like are controlled based on the monitoring results.

[0074] In the plasma treatment process, the plasma current density at the intermediate position between the LA71 and the workpiece film W is preferably 1.0 mA / cm 3 More preferably, 2.0 mA / cm 3 More preferably, 3.0 mA / cm 3 More than 10 mA / cm 3 Less than or equal to 8mA / cm 3 Less than 4 mA / cm, more preferably 3The following is the results. Inductive coupling type plasma processing using a low inductance antenna can achieve a higher plasma current density (for example, a plasma density about 100 times higher) than the capacitive coupling type plasma processing. When the plasma current density is equal to or higher than the lower limit, sufficient plasma oxygen particles can be secured in the plasma processing chamber C2 during plasma processing, and the surface of the workpiece film W can be appropriately modified. When the plasma current density is equal to or lower than the upper limit, damage to the workpiece film W caused by excessively high density plasma oxygen particles can be suppressed during plasma processing. Methods for adjusting the plasma current density include, for example, adjusting the amount of oxygen gas introduced into the plasma processing chamber C2, adjusting the frequency of the high frequency power in the high frequency power supply, and adjusting the magnitude of the applied power.

[0075] By subjecting the hard coat film X' to the above-described plasma treatment, a hard coat film X having an HC layer 12 is produced as shown in Fig. 4B. By not carrying out the next film-forming step, a hard coat film X having no inorganic layer formed on the HC layer 12 is obtained.

[0076] In the film forming step, following the plasma treatment step, an inorganic layer 20 is formed on the HC layer 12 of the workpiece film W (hard coat film X) by sputtering in a reduced pressure atmosphere. The reduced pressure atmosphere is preferably a vacuum.

[0077] In the sputtering method, a sputtering gas (inert gas) is introduced into each sputtering chamber 60 through one second line, while a negative voltage is applied to a target (film forming material) arranged on a cathode 61 in the sputtering chamber 60. This generates a glow discharge to ionize gas atoms, and the gas ions collide with the target surface at high speed, ejecting the target material from the target surface, and depositing the ejected target material on the workpiece film W. Examples of sputtering gases include argon, krypton, and xenon.

[0078] When the deposition material is a metal oxide, the sputtering method may be a reactive sputtering method. In the reactive sputtering method, oxygen (reactive gas) is introduced into the sputtering chamber 60 in addition to the sputtering gas. The oxygen is introduced into the sputtering chamber 60 through another second line. In the reactive sputtering method, the target is made of, for example, a metal in the metal oxide that forms each layer.

[0079] In the sputtering method, the pressure (second pressure) in the sputtering chamber 60 is, for example, 0.1 to 5.0 Pa depending on the type of layer to be formed. The film formation temperature (the temperature of the workpiece film W adjusted by the film formation roller 54) is, for example, -10°C to 150°C.

[0080] In the film forming step, next, the inorganic layer 20 is formed on the HC layer 12 by a sputtering method in at least one sputtering chamber selected from the sputtering chambers 60a to 60e. For example, when manufacturing the laminated film Y shown in Fig. 3, the adhesive layer 21 is formed on the HC layer 12 in the sputtering chamber 60a, the high refractive index layer 22a is formed on the adhesive layer 21 in the sputtering chamber 60b, the low refractive index layer 22b is formed on the high refractive index layer 22a in the sputtering chamber 60c, the high refractive index layer 22c is formed on the low refractive index layer 22b in the sputtering chamber 60d, and the high refractive index layer 22d is formed on the high refractive index layer 22c in the sputtering chamber 60e.

[0081] In the device Z, after the plasma treatment process and the film forming process, the laminated film Y as the workpiece film W passes through the connecting chambers C5 and C6 and reaches the winding chamber R2, where it is wound up by the winding roller 52.

[0082] In this manner, a long laminate film Y can be produced. EXAMPLES

[0083] The present invention will be specifically described below with reference to examples. However, the present invention is not limited to the examples. In addition, the specific numerical values ​​of the blending amounts (contents), physical property values, parameters, etc. described below can be replaced with the upper limit (a numerical value defined as "equal to or less than") or lower limit (a numerical value defined as "equal to or more than") of the blending amounts (contents), physical property values, parameters, etc. corresponding to those described in the above-mentioned "Form for carrying out the invention".

[0084] Example 1 The hard coat film of Example 1 was produced by carrying out the following steps in order.

[0085] First, a hard coat layer was formed on one side of a triacetyl cellulose (TAC) film as a base film (HC layer formation process). Specifically, first, 100 parts by mass (solid content equivalent value) of a butyl acetate solution of an ultraviolet-curable acrylic urethane resin (product name "Luxidia 17-806", solid content concentration 80% by mass, manufactured by DIC Corporation), 5 parts by mass of a photopolymerization initiator (product name "Omnirad907", manufactured by IGM Resins), 0.03 parts by mass of a leveling agent (product name "GRANDIC PC4100", manufactured by DIC Corporation), and butyl acetate as a solvent were mixed to prepare a first resin composition with a solid content concentration of 75% by mass. Next, cyclopentanone was added as an additional solvent to the first resin composition to prepare a second resin composition with a solid content concentration of 50% by mass. Meanwhile, a long TAC film (length 100 m, width 340 mm, thickness 40 μm) was prepared. Next, the second resin composition was applied to one side of the TAC film to form a coating film. Next, this coating film was dried by heating and then cured by ultraviolet light irradiation. As a result, a hard coat (HC) layer having a thickness of 5 μm was formed on the TAC film. The heating temperature was 100° C., and the heating time was 60 seconds. For ultraviolet light irradiation, a high-pressure mercury lamp was used as a light source, and ultraviolet light with a wavelength of 365 nm was irradiated onto the coating film, with an integrated irradiation amount of 300 mJ / cm. 2 In this manner, a roll of the TAC film with an HC layer was produced as a hard coat film (before plasma treatment).

[0086] Next, while the base film with the HC layer was transported in a vacuum by a roll-to-roll method, the hard coat film was subjected to plasma treatment (plasma treatment process). In this process, an apparatus (first apparatus) capable of performing a roll-to-roll process on the work film was used. The first apparatus includes a payout chamber, a plasma treatment chamber, a film formation chamber, and a winding chamber. The payout chamber, the plasma treatment chamber (first plasma treatment), the film formation chamber, and the winding chamber are arranged in this order and communicate with each other. The payout chamber includes a payout roller. A roll of the hard coat film was set on the payout roller as the work film. The plasma treatment chamber includes a temperature-adjusting transport roller (transport roller 53 in FIG. 5) and four low inductance antennas (LA71 in FIG. 6 and FIG. 7) covered with a cover block (cover block 73 in FIG. 7) as shown in FIG. 6 and FIG. 7. Each low inductance antenna has an extension portion (extension portion 71a in FIG. 6) parallel to the base film. In the four low inductance antennas, the extension length d1 is 88 mm, the maximum length d2 (length of the extension portion) is 100 mm, the separation distance d3 is 112 mm, the center distance d4 is 290 mm, and the center distance d5 is 280 mm (FIGS. 6 and 7). Each low inductance antenna is electrically connected to a high frequency power source (RF power source, frequency 13.56 MHz) via an impedance matching device outside the plasma processing chamber. The separation distance d' between the base film traveling in the plasma processing chamber and the cover block is 100 mm. The film formation chamber is a sputtering film formation chamber, and includes a film formation roller and a cathode arranged opposite the film formation roller. The winding chamber includes a winding roller.

[0087] Specifically, in this process, the hard coat film was transported from the unwinding chamber to the winding chamber by a roll-to-roll method, while the HC layer surface of the hard coat film was plasma treated in the plasma treatment chamber (plasma treatment process). The running speed of the hard coat film (film running speed) was 1.0 m / min. The temperature of the temperature-adjustable transport roller was -8°C. The conditions for the plasma treatment were as follows.

[0088] The ultimate vacuum level of the plasma processing chamber is 1.0×10 -4 After evacuating the inside of the apparatus until the pressure reached 0.5 Pa, oxygen gas was introduced into the plasma treatment chamber, and the pressure in the plasma treatment chamber was set to 0.5 Pa. By applying high-frequency power of 5.0 kW to the four low-inductance antennas by a high-frequency power source, an inductively coupled plasma of an oxygen-containing gas was formed around the antennas (the HC layer surface of the hard coat film was treated with this plasma).

[0089] In the manner described above, the hard coat film of Example 1 was produced. The hard coat film of Example 1 includes a substrate film and an HC layer on the substrate film. In the hard coat film of Example 1, the surface of the HC layer is plasma-treated. This plasma treatment is a treatment by inductively coupled plasma using an oxygen-containing gas generated by application of high-frequency power to a low-inductance antenna (oxygen-LAICP treatment).

[0090] Comparative Example 1 Except for not carrying out the above plasma treatment, a hard coat film (TAC film / HC layer) of Comparative Example 1 was produced in the same manner as the hard coat film of Example 1. In the hard coat film of Comparative Example 1, the surface of the HC layer was not plasma treated.

[0091] Comparative Example 2 First, an HC layer was formed on one side of a TAC film in the same manner as in the HC layer formation step in Example 1. In this way, a roll of a substrate film with an HC layer was obtained as a hard coat film (before plasma treatment).

[0092] Next, while the hard coat film was transported in a vacuum by a roll-to-roll method, the hard coat film was subjected to plasma treatment (plasma treatment process). In this process, a second device capable of performing a process of the roll-to-roll method on the work film was used. The second device has the same configuration as the first device, except that it has a second plasma treatment chamber instead of the first plasma treatment. The second plasma treatment chamber has a cathode electrode and an anode electrode (both rectangular electrodes made of SUS304) as a pair of flat electrodes for generating plasma. The pair of flat electrodes are arranged parallel to the base film passing through the second plasma treatment chamber with a gap of 50 mm. The anode electrode is arranged at a position 35 mm away from the base film passing through the second plasma treatment chamber, and is grounded outside the second plasma treatment chamber. The cathode electrode is arranged so as to face the HC layer surface of the base film, and is electrically connected to a high-frequency power source (RF power source, 13.56 MMHz) via an impedance matching device. The length of each electrode facing the base film in the film running direction is 110 mm, and the length in the width direction is 430 mm.

[0093] Specifically, in this process, the hard coat film was transported from the unwinding chamber to the winding chamber by a roll-to-roll method, and the HC layer surface of the hard coat film was subjected to plasma treatment (bombardment treatment) in the second plasma treatment chamber. The running speed of the base film (film running speed) was 1.0 m / min. The conditions of the plasma treatment were as follows.

[0094] The ultimate vacuum in the second plasma processing chamber is 1.0×10 -4 After evacuating the inside of the device until the pressure reached 0.5 Pa, argon was introduced into the second plasma treatment chamber, and the pressure in the plasma treatment chamber was set to 0.5 Pa. Capacitively coupled plasma (CCP) was generated by applying a power of 550 W between the flat electrodes by a high-frequency power source. In this plasma environment, the HC layer surface of the hard coat film was bombarded with argon ions (Ar-BB treatment).

[0095] In this manner, a hard coat film of Comparative Example 2 was produced. The surface of the HC layer of the hard coat film of Comparative Example 2 was plasma-treated. This plasma treatment was an ion bombardment treatment (Ar-BB treatment) by capacitively coupled plasma using argon gas.

[0096] <Surface texture> The surface properties of the HC layer surface were examined for each of the hard coat films of Example 1 and Comparative Examples 1 and 2. Specifically, first, the exposed surface of the HC layer in the hard coat film was observed and imaged using an atomic force microscope (product name "Dimention Edge SPC-160113-01", manufactured by Bruker). In the observation, the measurement mode was set to tapping mode, and an antimony-doped Si cantilever (product name "RTESP-300", manufactured by Bruker) was used as a probe. Next, the surface roughness (arithmetic mean height based on ISO 25178-2:2012) Sa of the HC layer surface was obtained from the observation image of a 1 μm square. The surface roughness Sa is shown in Table 1.

[0097] <Surface free energy> For each of the hard coat films of Example 1 and Comparative Examples 1 and 2, the surface free energy of the HC layer surface was determined as follows.

[0098] First, a sample film of a predetermined size was cut out from the hard coat film. Next, the sample film was placed on a horizontally placed slide glass. Specifically, the sample film was placed on the slide glass so that the HC layer surface of the sample film was facing upward. Next, 2 μL of a predetermined liquid was dropped onto the HC layer surface of the sample film on the slide glass in an atmosphere of 23° C. and 50% relative humidity to form a droplet (droplet formation). Next, the contact angle of the droplet with respect to the sample film surface (HC layer surface) was measured using a contact angle meter (product name "DMs-401", manufactured by Kyowa Interface Science Co., Ltd.) (contact angle measurement). As the liquids, water (H2O), methylene iodide (CH2I2), and 1-bromonaphthalene were used. For each liquid, a series of operations including droplet formation and subsequent contact angle measurement were performed five times. The measurement was performed within 24 hours after the preparation of the hard coat film. The average of the five measurements for each liquid was taken as the contact angle with that liquid. In this manner, the contact angle θw of water, the contact angle θi of methylene iodide, and the contact angle θb of 1-bromonaphthalene of the sample film were obtained.

[0099] Next, for each sample film, the contact angle of water θw, the contact angle of methylene iodide θi, and the contact angle of 1-bromonaphthalene θb are used to solve the three simultaneous equations in the Kitazaki-Hata theory to obtain the surface free energy γ = γ d +γ p +γ h In the formula, γ d ,γ p ,γ h The Kitazaki-Hata theory is described, for example, in the Journal of the Japan Adhesion Association, Vol. 8, No. 3, p. 131-141 (1972). d is the dispersion component of the surface free energy, and γ p is the polar component of the surface free energy, and γ h is the hydrogen bonding component of the surface free energy, and γ d ,γ p ,γ hThe value (γ) obtained by adding up the above values ​​was determined as the surface free energy of the HC layer surface of the sample film. The dispersion component γ d is 29.1 mN / m, and the polar component γ p is set to 1.3 mN / m, and the hydrogen bond component γ h The dispersion component γ in the surface free energy of methylene iodide was d is 46.8mN / m, and the polar component γ p is set to 4.0 mN / m, and the hydrogen bond component γ h was set to 0.0 mN / m. The dispersion component γ in the surface free energy of 1-bromonaphthalene d is 44.4 mN / m, and the polar component γ p is set to 0.1 mN / m, and the hydrogen bond component γ h was set to 0.0 mN / m. The surface free energy (mN / m) of the HC layer surface of the sample film is shown in Table 1.

[0100] <Softening temperature of HC layer surface> For each of the hard coat films of Example 1 and Comparative Examples 1 and 2, the softening temperature of the HC layer surface was measured (first measurement) as follows.

[0101] First, a measurement sample was prepared. Specifically, a film piece of a predetermined size was cut out from the hard coat film. Next, the base film side of the film piece (the side opposite to the HC layer surface) was attached to a plate via a strong adhesive. This resulted in a measurement sample.

[0102] Next, the measurement sample was set on the measurement table of a nano thermal analyzer (product name "AFM5300 / NanoTA-2", manufactured by Hitachi High-Tech Science Corporation). The HC layer surface of the measurement sample on the measurement table was exposed upward. Nano thermal analysis was then performed using the nano thermal analyzer. In this analysis, a cantilever (product name "AN2-300", manufactured by Hitachi High-Tech Science Corporation) was used as a probe to be pressed against the HC layer surface of the measurement sample. The measurement mode was set to nano TA mode, and the measurement range was set to 8 μm square. In this analysis, one cycle including the following steps 1 and 2 was repeated multiple times.

[0103] Step 1: As shown in FIG. 8, the tip Pa of a cantilever P (probe) was brought into contact with the surface (12a) of the HC layer (12).

[0104] Step 2: The temperature of the cantilever P (including the tip Pa) was raised from room temperature at a rate of 5° C. / sec, and when it reached the set temperature t (° C.), the cantilever P was released from the surface.

[0105] In the first cycle, the set temperature t was set to a temperature that was considered to be significantly lower than the softening temperature of the HC layer surface. For each cycle (steps 1 and 2), the contact point (step 1) of the cantilever with respect to the HC layer surface was changed, and the set temperature t (step 2) was raised by 2°C. In the last cycle, the set temperature t was set to a temperature that was considered to be significantly higher than the softening temperature of the HC layer surface. In step 2, the part of the surface 12a of the HC layer 12 where the tip Pa of the cantilever P is in contact is locally heated and expands. If the set temperature t is lower than the softening temperature of the surface 12a, the tip Pa does not penetrate the surface 12a. If the set temperature t is equal to or higher than the softening temperature of the surface 12a, the tip Pa penetrates the surface 12a.

[0106] Next, the HC layer surface was observed with a nano thermal analyzer to confirm the presence or absence of cantilever penetration marks at each cantilever contact site. When penetration marks were observed at the cantilever contact site on the HC layer surface in three consecutive cycles, the lowest set temperature t in those three cycles was determined as the softening point temperature. The softening temperature measured in this way is shown in Table 1 as the softening temperature T1 (°C) of the HC layer surface.

[0107] For each of the hard coat films of Example 1 and Comparative Examples 1 and 2, the softening temperature of the HC layer surface after the plasma treatment test described below was measured (second measurement). The measured softening temperature is shown in Table 1 as the softening temperature T2 (°C) of the HC layer surface after the plasma treatment test. The difference (T2-T1) between the softening temperature T2 and the softening temperature T1 is also shown in Table 1.

[0108] Plasma treatment test: The surface of the hard coat layer is treated with inductively coupled plasma of oxygen gas generated by applying high frequency power of 13.56 MHz and 5.0 kW to the low inductance antenna. More specifically, this plasma treatment was carried out in the same plasma treatment chamber under the same conditions as those in the plasma treatment step described above in relation to Example 1.

[0109] <Adhesion> After forming an inorganic layer on each of the hard coat films of Example 1 and Comparative Examples 1 and 2 to obtain a laminate film, the following first and second tests were carried out to examine the adhesion of the inorganic layer.

[0110] In forming the inorganic layer, an apparatus equipped with a sputtering deposition chamber capable of sputtering by a roll-to-roll method was used. The sputtering deposition chamber is equipped with a deposition roller (deposition roller 54 in FIG. 5) and first and second sputtering chambers (sputtering chambers 60a, 60b in FIG. 5). Each sputtering chamber is a partitioned space within the deposition chamber. The first and second sputtering chambers are arranged in this order along the circumferential direction of the deposition roller and in the running direction of the substrate film. Each sputtering chamber is equipped with a cathode arranged opposite the deposition roller. A required number of second lines (not shown) equipped with flow rate control valves for introducing gas into the chamber are connected to each sputtering chamber.

[0111] In forming the inorganic layer on the hard coat film, first, while the substrate film was cooled and transported by the deposition roll in the deposition chamber, an adhesive layer was formed on the HC layer of the substrate film in the first sputtering chamber, and an inorganic layer was formed on the adhesive layer in the second sputtering chamber. The deposition temperature (temperature of the deposition roll) was -8°C. More specifically, it is as follows.

[0112] In the first sputtering chamber, a 5 nm thick ITO layer was formed as an adhesive layer by sputtering (adhesive layer formation process). In this process, the ultimate vacuum in the film formation chamber was 1.0×10 -4After the chamber was evacuated to 1000 MPa, argon was introduced as an inert gas into the first sputtering chamber, and the pressure in the first sputtering chamber was set to 0.3 Pa. A sintered body of indium oxide and tin oxide (ITO with a tin oxide concentration of 10 mass%) was used as the target. A DC power supply was used as the power supply for applying a voltage to the target. The discharge power was 1.0 kW. In the second sputtering chamber, a 20 nm thick SiO2 layer was formed by reactive sputtering. In this process, after the deposition chamber was evacuated as described above, argon as an inert gas and oxygen as a reactive gas were introduced into the second sputtering chamber, and the pressure in the second sputtering chamber was set to 0.3 Pa. The amount of oxygen introduced per 100 parts by volume of argon introduced into the second sputtering chamber was 30 parts by volume. A Si target was used as the target. A MF-AC power supply (60 kHz) was used as the power supply for applying a voltage to the target. The discharge power was 3.0 kW. After the inorganic layer was formed on the hard coat film in the manner described above, the following first and second tests were carried out.

[0113] Test 1: First, the substrate film side of the laminated film was fixed to a glass plate. Next, the inorganic layer of the laminated film on the glass plate was irradiated with light at a temperature of 85°C, a relative humidity of 45%, and an irradiation intensity (integrated illuminance at 290 to 450 nm) of 150 mW / cm. 2 The specimen was exposed to light from a metal halide lamp for 32.5 hours under the above conditions (accelerated weather resistance test). This test was carried out using Iwasaki Electric's "Eye Super UV Tester SUV-W161."

[0114] Test 2: First, eleven parallel first incisions (1 mm apart) extending linearly in a first direction and eleven parallel second incisions (1 mm apart) extending linearly in a second direction perpendicular to the first direction were made with a cutter knife in the inorganic layer of the laminated film on the glass plate after the first test, and 100 grids were formed by the first and second incisions. Next, isopropyl alcohol was continuously dripped at 2 mL / min on the 100 grid areas of the laminated film while a polyester wiper (trade name "Anticon Gold", manufactured by Sanplatec Co., Ltd.) was slid over the wiper contact surface of 20 mm x 20 mm, a load of 1.5 kg / 20 mm, a sliding speed of 50 mm / sec, and 1000 reciprocations. Next, 0.25 mm out of the 100 grids were cut. 2 The number of squares in which the above peeling occurred was counted, and the counted number was then divided by 100 to calculate the peeling rate (%).

[0115] A peeling rate of 5% or less was evaluated as “good,” and a peeling rate of more than 5% was evaluated as “bad.” The results are shown in Table 1.

[0116] [evaluation] In the hard coat film of Comparative Example 1, the HC layer does not contain particles, so the surface of the HC layer does not have unevenness due to particles. In the manufacturing process of the hard coat film of Comparative Example 1, the HC layer surface is not plasma treated. The surface roughness Sa of the HC layer of such a hard coat film of Comparative Example 1 is 0.35 nm, which is significantly lower than 0.80 nm. In addition, in the hard coat film of Comparative Example 1, the HC layer is a cured layer of a composition containing an ultraviolet curable resin, and the difference in softening temperature (T2-T1) of the HC layer surface is 32°C, which is significantly higher than 5°C. That is, the HC layer in Comparative Example 1 has a fragile thin layer on the surface and in the vicinity thereof. Therefore, the adhesion of the inorganic layer could not be ensured in the hard coat film of Comparative Example 1.

[0117] In the hard coat film of Comparative Example 2, the HC layer does not contain particles, so the surface of the HC layer does not have unevenness caused by particles. In the manufacturing process of the hard coat film of Comparative Example 2, the HC layer surface is bombarded with argon ions (Ar-BB treatment). The surface roughness Sa of the HC layer of such a hard coat film of Comparative Example 2 is 0.32 nm, which is significantly lower than 0.80 nm. In addition, in the hard coat film of Comparative Example 2, the HC layer is a cured layer of a composition containing an ultraviolet curable resin, and the difference in softening temperature (T2-T1) of the HC layer surface is 16°C, which is significantly higher than 5°C. That is, the HC layer in Comparative Example 2 has a fragile thin layer on the surface and in the vicinity thereof. Therefore, the adhesion of the inorganic layer could not be ensured in the hard coat film of Comparative Example 2.

[0118] In the hard coat film of Example 1, the HC layer of the base film does not contain particles, so the HC layer surface does not have unevenness caused by particles. However, in the manufacturing process of the hard coat film of Example 1, the HC layer surface is treated with inductively coupled plasma using an oxygen-containing gas generated by applying high-frequency power to a low-inductance antenna (oxygen-LAICP treatment). Compared with the Ar-BB treatment, the oxygen-LAICP treatment can roughen the HC layer surface with fine unevenness on the nanometer order. In addition, the oxygen-LAICP treatment can effectively remove the brittle thin layer on the HC layer surface. This is shown by the difference in softening temperature (T2-T1) of the HC layer surface in Example 1 being 5°C or less. Therefore, the adhesion of the inorganic layer was ensured in the hard coat film of Example 1.

[0119] [Table 1] [Explanation of symbols]

[0120] X Hard Coat Film Y laminated film H Thickness direction D plane direction 11 Base film 12 Hard coat layer (HC layer) 12a surface 20 Inorganic layer 21 Adhesion layer 22a, 22c High refractive index layer 22b, 22d Low refractive index layer

Claims

1. A hard coat film comprising a substrate film and a hard coat layer on the substrate film, the hard coat layer is a cured layer of a composition containing an ultraviolet curable resin, the surface roughness Sa of the hard coat layer on the surface opposite to the substrate film is 0.80 nm or more and 4.50 nm or less; The softening temperature of the surface of the hard coat layer is T 1 and The softening temperature T of the surface after the following plasma treatment test 2 and the softening temperature T 1 The hard coat film has a temperature difference of 5° C. or less. Plasma treatment test: The surface of the hard coat layer is treated with inductively coupled plasma of oxygen gas generated by applying high frequency power of 13.56 MHz and 5.0 kW to a low inductance antenna.

2. 2. The hard coat film according to claim 1, wherein the ultraviolet curable resin is at least one selected from the group consisting of an ultraviolet curable acrylic urethane resin and an ultraviolet curable acrylic resin.

3. The softening temperature T 1 The hard coat film according to claim 1 , wherein the hard coat film has a melting point of 105° C. or higher.

4. The softening temperature T 1 The hard coat film according to claim 1 , wherein the hard coat film has a melting point of 150° C. or less.

5. The hard coat film according to any one of claims 1 to 4, and an inorganic layer on the hard coat layer of the hard coat film.

Citation Information

Patent Citations

  • Plasma processing apparatus

    JP2020196934A

  • Transparent electroconductive laminate

    WO2016117610A1

  • Optical film with Anti-fouling layer and method for manufacturing same

    WO2023120158A1

  • Antireflection film and image display unit

    JP2022065437A